PENERAPAN MODEL PEMBELAJARAN “PROJECT BASED LEARNING (PBL)” PADA PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS VIII SMP DAYA CIPTA MEDAN - Depitaria Br Barus; Helena Agustiani Maharaja; Nabilla Putri Lesmana; Perida Roma Asi Siahaan; Elza Leyli Lisnora Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to enhance students’ speaking skills through the implementation of the Project-Based Learning (PBL) model in Indonesian language instruction for Grade VIII students at SMP Daya Cipta Medan. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 25 students of Class VIII A. Data were collected through classroom observations, speaking performance tests, interviews, and documentation. The findings indicate that the application of PBL had a positive and significant impact on students’ speaking skills, as evidenced by improvements in student participation, confidence, fluency, intonation, diction accuracy, and the ability to convey ideas coherently and systematically. Learning mastery, which was initially only 24% in the pre-cycle stage, increased substantially by the end of Cycle II. These results demonstrate that Project-Based Learning is an effective instructional model for developing students’ speaking skills in Indonesian language learning.